NUNANGAT AND BEYOND:: ACCULTURATION AND THE RETAINMENT OF INUIT IDENTITY IN CANADA (Canadian Journal of Native Studies, 2026)
Examining how acculturative changes affect Inuit culture—especiallylifestyle, customs, Inuktut language proficiency, andintellectual endeavours—I assess Inuit culture and identitywithin the fabric of multicultural Canada. Taking John W.Berry’s Fourfold Model of acculturation as an investigativeframework, I use Peter Weinreich’s Identity Structure Analysisto study the effects of acculturation on Inuit living in bothArctic Canada and the South. I propose that access to Southernculture for a people with strong attachment to the land transformspersonal and collective identity and creates amalgamatedidentities—especially for Inuit relocated to urban settings—which reflect both tradition and acculturative build-up. Theofficial recognition of the Inuit Nunangat, the homeland, wasa fundamental necessity for positive self-image and is a drivingforce today in asserting a uniquely Inuit identity within thecultural context of Canada. Building on Inuit-led amendmentsto the curriculum already in place across the North, I propose aheritage language-based and traditional knowledge-enhancedschool curriculum implementing the teaching of traditionaltexts, such as myths, classic tales, and songs in Inuktut in orderto foster traditional knowledge—known as IQ, or Inuit Quaujimajatuqangit—and Inuktut fluency, which are vital aspectsof cultural retainment for Inuit in Canada.